UPAYA PENINGKATAN KEMAMPUAN KEGIATAN PEMBELAJARAN MELALUI SUPERVISI AKADEMIK BAGI GURU SEKOLAH DASAR NEGERI NOMOR 14/II PASAR RANTAU EMBACANG - Heni Pudyastuti (Pendidikan Matematika | STKIP YM Bangko, 2019)
This study purfose to see how efforts to improve the ability of learning activities through academic supervision of six teachers of Public Elementary School No. 14 / II Rantau Embacang Market, Tanah Sepenggal District. This research is a field research that applies a qualitative descriptive approach. The procedures in this study are carried out in the form of four stages: planning, action, observation and reflection. The results showed that there was an increase in teacher behavior from cycle 1 to cycle 2. Furthermore, the results of the study showed an increase in evaluation through the APKG cycle 1 instrument with a value of 3, 33 (three point thirty three) to 3.56 (three point fifty six) in cycle 2. Keywords: Learning Quality, Academic Supervision